View of a fair ground with tents and vehicles - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A panoramic view of an unidentified fair grounds with several large white canvas tents. The main tent has wood seating under the tent top, and there are several people gathered in front of the main tent. On the far left, the roof tops of several wood buildings are visible and there are several smaller tents and parked vehicles. On the far right, different groups of people can be seen standing near the vehicles and beyond the main tent.